The Influence of Public Self-Awareness and Creative Content on Instagram Toward Consumer Purchase Intention - Syafe’i, Fathurrahman; Pandjaitan, Dorothy Rouly Haratua (LPPPIPublishing, 2025)
This study examines how public self-awareness and creative Instagram content influence consumer purchase intention toward Café Moroloko in Bandar Lampung. Using a quantitative explanatory approach with a cross-sectional online survey, data were gathered from 115 respondents selected through purposive sampling. Primary data were collected via online questionnaires, supported by relevant secondary sources. The analysis included validity and reliability tests, followed by multiple linear regression. Hypothesis testing using the t-test and F-test showed that both public self-awareness and creative Instagram content have a positive and significant effect on purchase intention. The F-test confirmed the overall model significance, and the R² value indicated that these variables explain a substantial portion of the variance in purchase intention. The findings imply that enhancing consumers’ self-presentation tendencies and producing visually appealing Instagram content can effectively strengthen their intention to purchase or visit Café Moroloko. Further studies may explore additional influencing factors.